2023
DOI: 10.1101/2023.06.24.23291169
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Strong Genetic Overlaps Between Dimensional and Categorical Models of Bipolar Disorders in a Family Sample

Abstract: Objective: To determine the heritability and genetic relationships between dimensional and categorical models of bipolar disorder (BD). Methods: The Mood Disorder Questionnaire (MDQ) assesses lifetime history of cardinal manic symptoms and associated impairment. MDQ were collected from participants in the Amish-Mennonite Bipolar Genetics (AMBiGen) study, which enrolls individuals with BD and their relatives from Amish and Mennonite communities in North and South America. Principal Component Analysis (PCA) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
(71 reference statements)
0
0
1
Order By: Relevance
“…The authors suggest that MDQ may capture symptoms of general distress or psychopathology rather than hypomania/mania, specifically in at-risk populations [ 31 ]. However, these results contrast with those from another study that found a strong association between the MDQ score and a (different) pool of genetic risk factors [ 32 ]. An explanation for these contrasting results may be that the pools of genetic variants analyzed in the studies may not be the expression of a single risk, and that the disorder (of which the common syndrome is known, but a common pathogenesis is not) may be the result of the interaction of complex (and even non-unique) risk pathways.…”
Section: Introductioncontrasting
confidence: 99%
“…The authors suggest that MDQ may capture symptoms of general distress or psychopathology rather than hypomania/mania, specifically in at-risk populations [ 31 ]. However, these results contrast with those from another study that found a strong association between the MDQ score and a (different) pool of genetic risk factors [ 32 ]. An explanation for these contrasting results may be that the pools of genetic variants analyzed in the studies may not be the expression of a single risk, and that the disorder (of which the common syndrome is known, but a common pathogenesis is not) may be the result of the interaction of complex (and even non-unique) risk pathways.…”
Section: Introductioncontrasting
confidence: 99%